Functional Network Development in Sagittal Craniosynostosis Treated With Whole Vault Cranioplasty. Issue 5 (July 2021) - Cabrejo, Raysa; Lacadie, Cheryl; Sun, Alexander; Chuang, Carolyn; Yang, Jenny; Brooks, Eric; Beckett, Joel; Eilbott, Jeffrey; Gabrick, Kyle; Steinbacher, Derek; Duncan, Charles; DiLuna, Michael; et al.
Abstract : Introduction: In this study, the authors seek to clarify the neurological changes before and after whole vault cranioplasty (WVC) in patients born with sagittal craniosynostosis. Methods: A case control study design was performed that included thirty functional MRI scans, from 25 individual patients. Functional MRI and diffusion tension imaging data were analyzed with BioImageSuite (Yale University, USA). 9 functional brain networks were analyzed, with appropriate correlated functional regions of the brain and utilized for analysis. Results: Comparing functional MRI the infants after WVC versus infants before WVC group, the after WVC group demonstrated an increased connectivity in the left frontoparietal, secondary (V2), and third (V3) visual networks ( P  < 0.001). The right frontoparietal (RFPN) had decreased connectivity ( P  < 0.001). There is also a decrease and increase in anisotropy in the cingulum and precuneus despite surgery, respectively ( P  < 0.05). Adolescents treated with WVC compared to controls, demonstrated an increased connectivity in the salience and decreased connectivity in the RFPN relative to adolescent controls. Conclusions: Patients born with sagittal craniosynostosis have different connections in infancy in most of the defined cerebral networks compared to controls. After surgery, there are specific connectivity changes that occur in the RFPN, left frontoparietal, V2, and V3 networks, which are areas associated with executive function and emotional control. Changes identified in white matter tract microstructure connections could be influential in changes in functional connectivity. Although, as a child with sagittal craniosynostosis develops, much of the abnormal network connections, seen in infancy preoperatively, corrects to some degree after surgery. However, some aberrancies in the salience and RFPN networks remain potentially affecting executive functioning. Abstract : Supplemental Digital Content is available in the text